KORELASI KADAR FERRITIN DAN KADAR IL-6 TERHADAP SATURASI OKSIGEN PADA PASIEN COVID-19 DI RUMAH SAKIT ADVENT BANDUNG - Tania, Monica; Nurhayati, Betty; Hayati, Eem; Durachim, Adang (Journal of Medical Laboratory and Science, 2025)
Background: Covid-19 was first discovered in late 2019 in Wuhan, China caused by the coronavirus-2 or SARS-Cov-2. This virus causes a cytokine storm characterized by hyperferritinemia and increased IL-6 levels. Most Covid-19 patients require ventilator assistance due to severe pneumonia, alveoli damage, lung parenchyma damage, and the occurrence of Acute Respiratory Distress Syndrome (ARDS) characterized by decreased oxygen saturation. Objective: to find a correlation between Ferritin levels and IL-6 levels on oxygen saturation. Methods: The type of research used is descriptive. The study population and samples were all patients of Advent Hospital Bandung who were admitted to the ICU room infected with Covid-19 with a positive PCR value with a CT value <40 and examined for Ferritin, IL-6 and oxygen saturation parameters in the period January-December 2021. And using the Spearman correlation statistical test. Results: It is known that the average Ferritin level is 1,528.04 ng/mL, the average IL-6 level is 238.35 pg/mL and the average oxygen saturation value has an average value of 90.1%, and there is a correlation between Ferritin levels and oxygen saturation of 29.7%, but there is no correlation between IL-6 levels and oxygen saturation. Conclusion: there is a correlation between Ferritin levels and oxygen saturation which has a weak level of relationship. Suggestion: Ferritin is recommended as an initial examination to indicate the good and bad condition of Covid-19 patients and can help clinicians in better and faster management of Covid-19 patients, because there is a relationship with oxygen saturation values.